International conferences on research and practices in science, technology and social science (i-crest) 2025 proceeding book - UiTM, Pusat Asasi (Pusat Asasi, UiTM Cawangan Dengkil, 2025)
The International Conference on Research and Practices in Science, Technology and Social Sciences (I-CReST) is an academic conference organised by the Centre of Foundation Studies, Universiti Teknologi MARA (UiTM), Selangor Branch, Dengkil Campus, Malaysia. Aligned with this year’s theme, “Synergy for Future Sustainability: Bridging Science, Technology, and Humanity”, the conference serves as a dynamic and pivotal virtual platform for researchers, scholars, and educational practitioners to engage in scholarly discourse, share the latest research findings, and foster collaborative networks. I-CReST strives to advance knowledge dissemination and facilitate intellectual discussions on diverse topics, with specific emphasis on transformative ideas that are aligned with science, technology, humanity, and their critical intersections in empowering and making education more sustainable. This conference has a typical format of 30- 50 minutes of presentations by plenary and keynote speakers, as well as invited presenters, who are experts in their respective fields. Interactive Q&A sessions subsequently follow the slots. To reach a wider audience, enhance accessibility, and promote greater academic engagement, the conference participants’ pre-recorded video presentations are streamed via Pusat Asasi UiTM’s YouTube Channel. Since its inaugural event in 2020, I-CReST has received tremendous positive responses, attracting diverse perspectives from academia and industry. I-CReST 2025 garnered a total of 122 abstracts and presentations on cutting-edge studies within the scopes of science, technology, and social sciences, as well as those of a cross-disciplinary nature. The conference also provides opportunities for publication in proceedings with an e-ISBN. Selected papers will be recommended for publication in journals indexed by WOS/Scopus/MyCite/MyJournal, following a thorough peer-reviewed process.